P3.195 Prevalence of syphilis and hiv infection during pregnancy in incarcerated women and the incidence of congenital syphilis in births in prison in brazil. (8th July 2017) - Domingues, Rosa Maria Soares Madeira; Leal, Maria Do Carmo; Esteves-Pereira, Ana Paula; Ayres, Barbara; Sanchez, Alexandra; Larouze, Bernard
Abstract : Introduction: This study aimed to estimate the prevalence of syphilis and HIV infection during pregnancy, the mother to child transmission (MTCT) of syphilis and the incidence of congenital syphilis in incarcerated women in Brazil; to compare these rates to those observed in pregnant women outside of jail; and to verify the maternal factors associated with syphilis infection during pregnancy in free and incarcerated women. Methods: We used data from two nationwide studies conducted during the period 2011–2014. The "Birth in Brazil" study included 23 894 free women cared for in 266 hospitals. The "Maternal and Infant Health in Prisons" study included 495 incarcerated pregnant women or mothers living with their children, according to a census conducted in 33 female prisons. The same case definitions and data collection methods were used in both studies. We used the Chi square test to compare the characteristics of incarcerated and free women with a significance of 0.05. Results: For incarcerated women, the estimated prevalence of syphilis during pregnancy was 8.7% (IC 95% 5.7–13.1) and for HIV infection 3.3% (IC 95% 1.7–6.6), rates almost 7 times greater than that found in free women. The estimated MTCT of syphilis was 66.7% (IC 95% 44.7–83.2) and the incidence of congenital syphilis at birth was 58.1 per 1000 living newborns (IC 95% 40.4–82.8), rates two and 12.6 times higher than in free women, respectively. Incarcerated women showed greater social vulnerability and worse results in all the evaluated antenatal indicators. Syphilis infection was associated with social vulnerability in free women, but not in incarcerated women. Conclusion: Incarcerated women had a higher prevalence of syphilis and HIV infection during pregnancy, lower quality of antenatal care and higher levels of social vulnerability. Health initiatives in the prison system are necessary to reduce healthcare inequalities and should include adequate antenatal and birth care with opportune diagnosis and treatment of infected pregnant women as recommended in national and international guidelines.